(untitled) (Journal of Mathematical Study, 2023)
This paper studies the weighted (L^p ,L^r)-boundedness for a class of multilinear oscillatory singular operators with real-valued polynomial phases and rough homogeneous kernels belonging to Llog^+L(S^ n−1), and establishes two criteria on the corresponding weighted bounds for such operators.